2019
DOI: 10.1101/825802
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of conserved proteomic networks in neurodegenerative dementia

Abstract: multiple independent data sets, up-regulated early in the disease course, and enriched in AD common genetic risk. In contrast to AD, PSP genetic risk was enriched in module C1, which represented synaptic processes, clearly demonstrating that despite shared pathology such as synaptic loss and glial inflammatory changes, AD and PSP have distinct causal drivers. These conserved, high confidence proteomic changes enriched in genetic risk represent new targets for drug discovery.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 151 publications
(139 reference statements)
0
6
0
Order By: Relevance
“…1g,h). Activation of cGAS-STING was further analyzed in previously published microarray profiles of hippocampi from 3-, 6-, 9-and 12-month-old P301S transgenic mice 17 . IRF and ISRE TF motifs were enriched in DEGs associated with tauopathy (Extended Data Fig.…”
Section: Cgas-sting Is Activated In Tau Transgenic Mice and Human Admentioning
confidence: 99%
“…1g,h). Activation of cGAS-STING was further analyzed in previously published microarray profiles of hippocampi from 3-, 6-, 9-and 12-month-old P301S transgenic mice 17 . IRF and ISRE TF motifs were enriched in DEGs associated with tauopathy (Extended Data Fig.…”
Section: Cgas-sting Is Activated In Tau Transgenic Mice and Human Admentioning
confidence: 99%
“…Considering that genes do not operate along, but rather within signaling pathways and networks, we and others have shown that better understanding of disease mechanisms can be achieved through gene network analysis [31][32][33] . Therefore, we scrutinized rare variants within a network framework, focusing on co-expression network analysis performed in PSP post mortem brain that had previously identified a brain co-expression module, C1, which was conserved at the protein interaction level and enriched for common variants in PSP 34 .…”
Section: Rare Snvs/indels and Network Analysismentioning
confidence: 99%
“…To understand how neural‐immune‐associated genes and pathways contribute to neurodegenerative disease pathophysiology, Rexach and colleagues conducted systematic functional genomic analyses of microglia and bulk tissue from mouse and human models of AD, FTD, and PSP 50 . An earlier bulk tissue RNA sequencing (RNAseq) study by the same team revealed that downregulated microglial gene expression trajectories were likely obscured by a general disease‐related upregulation of microglia 51,52 . Accordingly, the team designed a study that would reveal both upregulated and downregulated signaling pathways within microglia, to enable more precise identification of stage‐ and pathology‐associated microglial states.…”
Section: Introductionmentioning
confidence: 99%